Statelessness as a political-existential predicament in the lives and writings of three German-Jewish intellectuals - Musch, Sebastian (The historical journal, 2025)
This article investigates the writings of three German-Jewish intellectuals: Kurt Grossmann (1897-1972), Hannah Arendt (1906-75), and Günther Anders (1902-92). It argues that all three thinkers dealt, in their lives as well as their writing, with the construction of a common refugee polis. Yet this engagement was limited by a political-existential predicament that, through their attempts to reclaim their agency, turned their historical and philosophical works into a renegotiation of their own biographies. The article focuses on key chapters in Arendt’s The origins of totalitarianism, in conjunction with her essay We refugees; on Grossmann’s books The Jewish refugee (co-authored with Arieh Tartakower) and Emigration: the history of the Hitler-refugees 1933-1945; and on Anders’s essay ‘The emigrant’. As victims of National Socialism who fled from Nazi Germany to the US, these authors represent a distinctive view of the transition from the Second World War to the era of the Cold War. Reclaiming agency served as a way to resist subjugation by Nazi race ideology, yet it also circumscribed their belief in the radical potential of the political refugee, resulting in Arendt’s focus on totalitarianism, Grossmann’s limiting the refugee polis to Jewish refugee organizations, and Anders’s inward existential gaze.